Superior Thermoelectric Performance of Black Phosphorus in Elemental Tellurium. Issue 47 (26th October 2022) - Yang, Manman; Li, Xiangjun; Duan, Shuai; Zhang, Xiaoran; Sun, Hairui; Chen, Xin; Su, Taichao; Gu, Lin; Liu, Xiaobing
Abstract: Simple elemental thermoelectrics are an ideal platform to demonstrate fundamental physics in materials and develop new strategies for high‐efficiency energy conversion devices. Recently, black phosphorus (BP) is theoretically predicted as a superior thermoelectric candidate, however it meets a great challenge in practical application because of its poor stability. Here, it is reported that the BP phase can be stabilized from 300 to 610 K through creation of a heterojunction structure in Te‐based thermoelectrics, leading to simultaneously enhanced electrical behaviors and reduced thermal conductivity. The peak and average z T values at a temperature range of 300–610 K are increased by 49% and 30% in (Sb, Se, Ge)Te‐BP system, respectively. Maximum z T up to 1.1 at 610 K has been achieved, as the highest value in elemental Te‐based thermoelectrics throughout the measured temperature region. This study clarifies the multiple benefits of engineering a heterojunction structure in independently modulating the coupled parameters, and opens up a pathway searching high performance thermoelectric materials in BP‐based structures. Abstract : The superior thermoelectric performance of black phosphorus (BP), predicted by theoretical calculations, is first realized in elemental Te‐based materials by forming a heterojunction structure under high pressure and high temperature conditions. These simultaneously optimized electrical properties and reduced lattice thermal conductivity lead to significantly enhanced peak and average z T values, opening up a feasible routine for novel eco‐friendly thermoelectrics in BP‐related structures.